Evaluation of Uncertainty in Determination of Cephalosporins in Chicken by High Performance Liquid Chromatography-Tandem Mass Spectrometry Isotope Internal Standard Method - Xing XU; Yan ZHANG; Ping SHU; Weihua YANG; Haojun ZHAO; Yiyi DONG (Shipin gongye ke-ji, 2022)
In order to ensure the accuracy of test results, the uncertainty determination of cephalosporins in chicken by high performance liquid chromatography-tandem mass spectrometry isotope internal standard method was evaluated. The source of uncertainty was evaluated and the mathematical model was established. Through quantitative analysis of each component of uncertainty, the uncertainty of each component was calculated. Finally, standard uncertainty was composited. When the content of cephalosporins in the sample was 250 μg/kg, the expanded uncertainty was 43.60~50.10 μg/kg. The results showed that uncertainty mainly derived from the measuring instruments (0.0762), repeatability (0.0337), analytical instruments (0.0250) and the addition of internal standards (0.0224). Among them the measurement instrument contributed the most to the uncertainty. It provided a reference basis for uncertainty evaluation of determination of cephalosporins by high performance liquid chromatography-tandem mass spectrometry isotope internal standard method.